Isolation of Flavonoids from Walang Sangit Leaves (Eryngium Foetidum) Using Methanol and Acetone Maceration with UV–Visible Spectrophotometric Analysis - Suhirman Suhirman; Adna Ivan Ardian; Fikrah Dian Indrawati Sawali; Moh Azhar Afandy (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Flavonoids are natural phytonutrient compounds in plants that exhibit antioxidant properties and play a role in scavenging free radicals. Walang sangit leaves have potential as a source of flavonoids, with samples consisting of young and mature leaves obtained from Pagebangan, Ciwandan District, Cilegon City. The sample preparation stage was carried out through extraction using the maceration method. The experimental procedure involved 10 g of dried walang sangit leaves ground to 60 mesh, which were macerated using 99.95 percent methanol and 80 percent acetone solutions. The volume of methanol and acetone used was 250 mL, with maceration times of 60 and 120 minutes in an Erlenmeyer flask. At 120 minutes, the methanolic extract yielded 2.81 mg QE/g (young leaves) and 4.12 mg QE/g (mature leaves), whereas the acetone extract only reached 1.03 mg QE/g and 2.88 mg QE/g, respectively. A similar pattern was also observed at 60 minutes, with methanol producing values of 1.39 – 2.32 mg QE/g, which were higher than those obtained with acetone (0.35 –0.78 mg QE/g). The highest extraction rate constant was obtained for acetone–mature leaves (0.0124 / min) and for methanol young leaves (0.0058 / min).